Life-cycle health effects of compulsory schooling - Schmitz, Hendrik; Tawiah, Beatrice Baaba
We study the effect of education on health (hospital stays, number of diagnosed conditions, self-rated poor health, and obesity) over the life-cycle in Germany, using compulsory schooling reforms as a source of exogenous variation. Our results suggest a positive correlation of health and education which increases over the life-cycle. We do not, however, find any positive local average treatment effects of an additional year of schooling on health or health care utilization for individuals up to age 79. An exception is obesity, where positive effects of schooling start to be visible around age 60 and become very large in age group 75-79. The results in age group 75-79 need to be interpreted with caution, however, due to small sample size and possible problems of attrition.
Keywords: Education; health; life-cycle effects; compulsory schooling

Housing Situations and Local COVID-19 Infection Dynamics – A Case Study With Small-Area Data - Freise, Diana; Schiele, Valentin; Schmitz, Hendrik
Keywords: General Earth and Planetary Sciences; General Environmental Science

The effect of compulsory schooling on vaccination against COVID and Influenza - Monsees, Daniel; Schmitz, Hendrik
We study the effect of education on vaccination against COVID-19 and influenza in Germany and Europe. Our identification strategy makes use of changes in compulsory schooling laws and allows to estimate local average treatment effects for individuals between 59 and 91 years of age. We find no significant effect of an additional year of schooling on vaccination status in Germany. Pooling data from Europe, we conclude that schooling increases the likelihood to vaccinate against COVID by an economically negligible effect of one percentage point (zero for influenza). However, we find indications that additional schooling increases fear of side effects from COVID vaccination.
Keywords: COVID; influenza; vaccination; education; compulsory schooling

Unboxing video effectiveness – Does speech matter? - Garnefeld, I.; Böhm, Eva; Hanf, L.; Helm, S. (2023 AMA Summer Academic Conference, San Francisco, CA)

The dark and bright side of online reviews in manufacturer online shops - Kessing, K.; Garnefeld, I.; Böhm, Eva (EMAC Annual Conference, Odense, Denmark)

Stimulating engagement with unboxing videos – Does speech matter? - Hanf, L.; Garnefeld, I.; Böhm, Eva; Helm, S. (EMAC Annual Conference, Odense, Denmark)

Bring me my Meal on your Wheel - An Empirical Analysis of the Impact of Food Delivery Platforms on Local Restaurant Employment - Müller, Michelle; Neumann, Jürgen (Proceedings of the 55th Hawaii International Conference on System Sciences (HICSS))

Digital technology usage as a driver of servitization paths in manufacturing industries - Harrmann, Lisa Katharina; Eggert, Andreas; Böhm, Eva (European Journal of Marketing)
Purpose This study aims to conceptually propose and empirically validate a path perspective on the servitization process of manufacturing firms. It identifies a customer and an outcome path to servitization, sheds light on the pivotal role of digital technology usage for both value-creating paths and explores their financial and relational performance outcomes. Design/methodology/approach The authors use a mixed-method approach, combining a qualitative study with a cross-sectional survey in the USA, the UK and Germany. Findings Manufacturing firms choose between two generic paths to servitization, a customer and an outcome path. Digital technology usage is equally important for both value-creating paths. Progress on the outcome path has a positive effect on firms’ financial performance, whereas the customer path has an indirect effect only, fully mediated by firms’ relational performance. Customer tenure and customer’s open-mindedness are contingency variables in the digital technology usage – servitization path – firm performance framework. Research limitations/implications A path perspective is useful to conceptualize the servitization processes in manufacturing industries. Future research should investigate the sequential choice of servitization paths and explore its drivers and performance outcomes. Practical implications To create and claim superior value for their customers, managers can choose between two servitization paths, leading to differential performance outcomes. While digital technology usage is key to progress on both paths, it is particularly effective for newly acquired customers on the customer path. Suppliers should target their value-creating service offerings at open-minded customer firms to reap their full performance potential. Originality/value Propose and empirically validate a path-perspective on servitization. Understand the pivotal importance of digital technology usage for both servitization paths.
Keywords: Marketing

Der Hauptschulabschluss als sozial selektiver Hauptzulieferer des Übergangssystems - Sommer, Christian (Berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)
Über zwei Drittel der Anfänger*innen im Übergangssystem verfügen maximal über einen Hauptschul-/Mittelschulabschluss. Sie sind damit überrepräsentiert, was sich weniger durch ihre Kompetenzen als mit ihrem sozioökonomischen Status und klassenspezifischen Nachqualifizierungsverhalten erklären lässt.
Keywords: Social inequality; Transition system

A Regret Policy for the Dynamic Vehicle Routing Problem with Time Windows - Dieter, Peter (Lecture Notes in Computer Science)

Housing situations and local COVID-19 infection dynamics using small-area data - Freise, Diana; Schiele, Valentin; Schmitz, Hendrik (Scientific Reports)
Abstract Low socio-economic status is associated with higher SARS-CoV-2 incidences. In this paper we study whether this is a result of differences in (1) the frequency, (2) intensity, and/or (3) duration of local SARS-CoV-2 outbreaks depending on the local housing situations. So far, there is not clear evidence which of the three factors dominates. Using small-scale data from neighborhoods in the German city Essen and a flexible estimation approach which does not require prior knowledge about specific transmission characteristics of SARS-CoV-2, behavioral responses or other potential model parameters, we find evidence for the last of the three hypotheses. Outbreaks do not happen more often in less well-off areas or are more severe (in terms of the number of cases), but they last longer. This indicates that the socio-economic gradient in infection levels is at least in parts a result of a more sustained spread of infections in neighborhoods with worse housing conditions after local outbreaks and suggests that in case of an epidemic allocating scarce resources in containment measures to areas with poor housing conditions might have the greatest benefit.
Keywords: Multidisciplinary

Implementing Digital Responsibility through Information Systems Research: A Delphi Study of Objectives, Activities, and Challenges in IS Research - Beverungen, Daniel; zur Heiden, Philipp; Lehrer, Christiane; Trier, Matthias; Bartelheimer, Christian; Bradt, Tobias; Distel, Bettina; Drews, Paul; Ehmke, Jan Fabian; Fill, Hans-Georg; Flath, Christoph M.; Fridgen, Gilbert; et al.

The Origination of Online Reviews in B2B Markets: A Qualitative Study on the Underlying Motives of Review Writers - Seutter, Janina

Wie Arbeitgeber strategisch gegen den Arbeitskräftemangel vorgehen. - Schneider, Martin; Radermacher, Katharina (Wie Arbeitgeber strategisch gegen den Arbeitskräftemangel vorgehen.)

The Role of Response Time for Algorithm Aversion in Fast and Slow Thinking Tasks - Lebedeva, Anastasia; Kornowicz, Jaroslaw; Lammert, Olesja; Papenkordt, Jörg (Artificial Intelligence in HCI)

Are Numbers or Words the Key to User Reliance on AI? - Papenkordt, Jörg; Ngonga-Ngomo, Axel-Cyrille; Thommes, Kirsten (Academy of Management Proceedings)

Employer Branding - Wie Arbeitgeber strategisch gegen den Arbeitskräftemangel vorgehen. - Schneider, Martin; Radermacher, Katharina (Die Politische Meinung)

A model of cycles and bubbles under heterogeneous beliefs in financial markets - Burs, Carina (Cogent Economics & Finance)
I study the effect of heterogeneous beliefs about asset prices on the long-term behavior of financial markets. Starting from the ideas of Abreu and Brunnermeier (Citation2003), a two-dimensional system of differential equations is developed. The first dynamic variable is the asset price growth rate. The second dynamic variable is the number of investors who believe that asset prices are abnormally high. In a phase plane analysis, I find both stable and unstable equilibria, depending on the spread of information and the response to other agents’ beliefs. If individuals try to increase their returns while perceiving more overpricing, these equilibria can be spirals or even approach limit cycles. Although I intend to study general price patterns, abnormally high asset prices can be caused by financial bubbles. In this model, bubbles can emerge and deflate both in cycles or directly, or they can grow until they burst. Further, I analyze market behavior after a central bank increases the interest rate. This can lead to new stable equilibria, but the emergence and bursting of bubbles cannot be prevented.
Keywords: asset pricing; subjective information; stability conditions; monetary policy; risk aversion

Frühe Versuche zur Etablierung des Hochschulstandorts Paderborn (1945-1970) - Grüttner, Niclas Christian (50 Jahre Universität Paderborn. Studentische Forschungsprojekte zur Gründungsgeschichte. Ein Rückblick)

The Choice of Ideology and Everyday Decisions - Burs, Carina; Gries, Thomas; Müller, Veronika (Journal of Organizational Psychology)
Individuals strive to make decisions that are consistent with not only their consumer preferences but also their psychological needs. However, they are confronted with complex, ambiguous or even false information. Ideologies and belief systems provide guidance when processing and evaluating information and give a coherent and comprehensible interpretation of reality. The first question is: why is an individual attracted to a particular ideology? Individuals choose ideologies that resonate with their subjective psychological needs and preferences. Second, how do individuals search for ideologies and find out which suit them best? We model an individual’s sequential information search for the best matching ideologies by applying Bayesian learning and utility optimization. Additional information enhances utility by reducing uncertainty. As a search is costly, the process may stop once an individual adopts an ideology even if the information set remains incomplete. Third, once they have chosen a particular ideology, individuals adhere to its rules and norms when making everyday decisions. Consumers not only physically consume, but they also act in accordance with their psychological needs.
Keywords: Economics; Ideology; Decision-making

Erlebnisorientiert Lehren und Lernen in der beruflichen Bildung. Entwicklung eines didaktischen Konzepts im Rahmen von designbasierter Forschung. - Volgmann, Simone

An IAD framework analysis of minigrid institutions for sustainable rural electrification in East Africa: A comparative study of Uganda and Tanzania - Namujju, Lillian Donna; Acquah-Swanzy, Henrietta; Ngoti, Irene F. (Energy Policy)
Keywords: Management; Monitoring; Policy and Law; General Energy

A Memetic NSGA-II for the Multi-Objective Flexible Job Shop Scheduling Problem with Real-time Energy Tariffs - Burmeister, Sascha Christian; Guericke, Daniela; Schryen, Guido (Flexible Services and Manufacturing Journal)

GBP-Monitor: Betriebswirtschaftliche Einschätzungen und Erwartungen von Unternehmen in Deutschland. Unternehmenstrends im November 2023 - Maiterth, Ralf; Sureth-Sloane, Caren; Dyck, Daniel; Heinemann-Heile, Vanessa

Frühe Versuche zur Etablierung des Hochschulstandorts Paderborn (1945-1970) - Grüttner, Niclas Christian (50 Jahre Universität Paderborn. Studentische Forschungsprojekte zur Gründungsgeschichte. Ein Rückblick)

Reviewing from a Distance: Uncovering Asymmetric Moderations of Spatial and Temporal Distances Between Sentiment Negativity and Rating - Neumann, Jürgen; Gutt, Dominik; Kundisch, Dennis (MIS Quarterly)

Collective Minimum Contributions to Counteract the Ratchet Effect in the Voluntary Provision of Public Goods - Alt, Marius; Kesternich, Martin; Gallier, Carlo; Sturm, Bodo (Journal of Environmental Economics and Management)
We experimentally test a theoretically promising amendment to the ratchet-up mechanism of the Paris Agreement. The ratchet-up mechanism prescribes that parties’ commitments to the global response to climate change cannot decrease over time, and our results show that its effect is detrimental. We design a public goods game to study whether cooperation is promoted by an amendment to the mechanism that stipulates that all agents must contribute at least a collectively chosen minimum based on the principle of the lowest common denominator. We find that binding collective minimum contributions improve the effectiveness of the ratchet-up mechanism. Non-binding minimum contributions, by contrast, do not encourage cooperation. Our data indicate that the difference is attributable to conditional cooperative dynamics. If other participants contribute less than the collective minimum contribution, even initially cooperative participants start to negatively reciprocate this form of non-compliance by contributing less.
Keywords: global public goods; climate change; institutions; ratchet-up mechanism; minimum contributions; laboratory experiment

Role (in-)congruity and the Catch 22 for female executives: how stereotyping contributes to the gender pay gap at top executive level - Diederich, Sarah; Iseke, Anja; Pull, Kerstin; Schneider, Martin (The International Journal of Human Resource Management)
Keywords: Management of Technology and Innovation; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management; Industrial relations

Inter-Charity Competition under Spatial Differentiation: Sorting, Crowding, and Spillovers - Gallier, Carlo; Goeschl, Timo; Kesternich, Martin; Lohse, Johannes; Reif, Christiane; Römer, Daniel (Journal of Economic Behavior and Organization)

Digital Responsibility – a Multilevel Framework for Responsible Digitalization - Beverungen, Daniel; Kundisch, Dennis; Mirbabaie, Milad; Müller, Oliver; Schryen, Guido; Trang, Simon Thanh-Nam; Trier, Matthias (Business & Information Systems Engineering)

Who Will Own Our Global Digital Twin: The Power of Genetic and Biographic Information to Shape Our Lives - Hellweg, Talea Davina; Schneider, Martin; Rückert, Ulrich; Harteis, Christian; Pilz, Sarah (The Digital Twin of Human)
Today, it is possible to collect and connect large amounts of digital data from various sources and life domains. This chapter examines the potential and the risks of this development from an interdisciplinary perspective. It defines the ‘global digital twin’ of a human being as the sum of all digitally stored information and predictive knowledge about a person. It points out that, compared to the digital twin of a machine, the human global digital twin is far more complex because it comprises the genetic code and the biographic code of a person. The genetic code contains not only a simple ‘construction plan’ but also hereditary information, in a form that is difficult to read. The biographic code contains all other information that can be assembled about a person, which is obtained via data from cameras, microphones, or other sensors, as well as general personal information. When the growing wealth of information concerning the genetic code and the biographical code is properly utilised, insights from biology and the behavioural sciences may be used to predict personal events such as health problems, job resignations, or even crimes. Because our own interests and those of private firms are partly in conflict over the use of this powerful knowledge, it is still unclear whether the global digital twins of humans will become a liberating or disciplining force for citizens. On the one hand, human beings are not machines: They are aware of their digital twin and therefore are able to influence it throughout their lives. Because of their free will, human beings are in general difficult to predict. Dystopias of full control over individual behaviour are therefore unlikely to materialise. On the other hand, private firms are beginning to take advantage of the available digital twins of humans by monopolising data access and by commercialising predictive knowledge. This is problematic because, unlike machines, human beings cannot only benefit from but also suffer due to their digital twins as they attempt to shape their own lives. We illustrate these issues with some examples and arrive at two conclusions: It is in the public interest for people to be granted more property rights over their personal global digital twins, and publicly funded research needs to become more interdisciplinary, much like private firms that have already begun to perform interdisciplinary research.

Integrating and Synthesizing Technostress Research: A Meta-Analysis on Technostress Creators, Outcomes, and Usage Contexts - Nastjuk, I.; Trang, S.; Grummeck-Braamt, J.; Adam, M.; Tarafdar, M. (European Journal of Information Systems)

The technology-behavioral compensation effect: Unintended consequences of health technology adoption - Wolf, T.; Trang, S.; Weiger, W.; Trenz, M. (Journal of Information Technology)

Deflected by the Tin Foil Hat? Word-of-Mouth, Conspiracy Beliefs, and the Adoption of Public Health Apps - Krämer, T.; Weiger, W.; Trang, S.; Trenz, M. (Journal of Product Innovation Management)

Should I Really do That? Using Quantile Regression to Examine the Impact of Sanctions on Information Security Policy Compliance Behavior - Hengstler, S.; Kuehnel, S.; Masuch, K.; Nastjuk, I.; Trang, S. (Computers & Security)

Aggregating Human Domain Knowledge for Feature Ranking - Kornowicz, Jaroslaw; Thommes, Kirsten (Artificial Intelligence in HCI)

Oh my Goodness: Investigating the Goodness of Performance Appraisal Formats Between and Within Teams - Gutt, Jana Kim; Mehic, Miro; Thommes, Kirsten (Academy of Management Proceedings)

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia Amelie; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

Die Doppelwirkung von Information für klimafreundliches Handeln - Frick, Marc; Foese, Dario; Von Graevenitz, Kathrine; Kesternich, Martin; Wagner, Ulrich
Informationen sind für eine erfolgreiche Klimapolitik in doppelter Hinsicht wichtig: Sie werden benötigt, wenn Potenziale zur Vermeidung von Emissionen identifiziert und klimapolitische Instrumente ausgewählt werden. Und sie sind zentral, damit Bürger/innen selbst Entscheidungen im Sinne des Klimaschutzes treffen können.
Keywords: General Medicine

Nonfinancial Reporting and Real Sustainable Change: Relationship Status—It’s Complicated - Hahn, Rüdiger; Reimsbach, Daniel; Wickert, Christopher (Organization & Environment)
The relationship between nonfinancial reporting and real sustainable change within and beyond organizations is fraught with complication. Furthermore, all facets of the relationship have not been examined equally. The contributions of this special issue made substantive progress in this regard and draw our focus to several remaining complications—in particular, the societal impacts of nonfinancial reporting. With this introduction, we seek to move the conversation forward by proposing a framework that disentangles the linkages between nonfinancial reporting and real sustainable change at multiple levels of analysis. We highlight the distinction between sustainability-related outputs and outcomes that typically materialize at the firm level, and eventually lead to sustainable impact at the societal level. Future research should advance this distinction and scrutinize the impact of real sustainable change beyond firm-level outputs, study the organizational change processes from antecedents to impacts, and examine the interrelationships between different instruments to foster real sustainable change.
Keywords: Organizational Behavior and Human Resource Management; General Environmental Science

﻿DARC 2023 at Radboud University: Societal challenges in accounting research and education - De Meyst, Karen; Niederkofler, Thomas; Reimsbach, Daniel (Maandblad voor Accountancy en Bedrijfseconomie)
This year, the 7th edition of the Dutch Accounting Research Conference (DARC) was hosted by the Nijmegen School of Management at Radboud University on Thursday, March 23. In total, over 75 accounting researchers from various Dutch universities were welcomed by Frank Hartmann, chair of the accounting group and head of the Business Economics department. During the day, four keynote speakers presented their research and in a panel discussion, the current state of accounting education was debated. In the evening, participants gathered to network over dinner. This article presents a discussion of the theme of the conference, an outline of the research papers and projects presented during the conference, and a summary of the panel discussion on Accounting Education.
Keywords: General Arts and Humanities

2022 Global MNC Tax Complexity Survey - Harst, Simon; Schanz, Deborah; Siegel, Felix; Sureth-Sloane, Caren

Towards Green Driving - Income Taxes Incentives for Plug-In Hybrids - Giese, Henning; Holtmann, Svea

Tax Complexity, Tax Department Structure, and Tax Risk - Giese, Henning; Koch, Reinald; Sureth-Sloane, Caren

The effectiveness of vaccination, testing, and lockdown strategies against COVID-19 - Fritz, Marlon; Gries, Thomas; Redlin, Margarete (International Journal of Health Economics and Management)
Abstract The ability of various policy activities to reduce the reproduction rate of the COVID-19 disease is widely discussed. Using a stringency index that comprises a variety of lockdown levels, such as school and workplace closures, we analyze the effectiveness of government restrictions. At the same time, we investigate the capacity of a range of lockdown measures to lower the reproduction rate by considering vaccination rates and testing strategies. By including all three components in an SIR (Susceptible, Infected, Recovery) model, we show that a general and comprehensive test strategy is instrumental in reducing the spread of COVID-19. The empirical study demonstrates that testing and isolation represent a highly effective and preferable approach towards overcoming the pandemic, in particular until vaccination rates have risen to the point of herd immunity.
Keywords: Health Policy; Economics; Econometrics and Finance (miscellaneous)

„Wir fahren jetzt nicht mit’m Mercedes vor, wenn man sich nachher eigentlich nur ‘n Polo leisten kann.“ Vorstellungen von Transfer in Theorie und Praxis der Beruflichen Bildung und ihre Implikationen - Daniel-Söltenfuß, Desiree

Zum Verständnis von Innovation und Transfer in einer vernetzten Berufsbildungspraxis. Ergebnisse einer übergreifenden Interviewstudie - Daniel-Söltenfuß, Desiree; Kückmann, Marie-Ann

„Go with the flow?!“ Einblicke in Forschungsansatz und erste Ergebnisse des Begleitforschungsprojekts ITiB - Daniel-Söltenfuß, Desiree; Kückmann, Marie-Ann

Do People Recover from Algorithm Aversion? An Experimental Study of Algorithm Aversion over Time - Leffrang, Dirk; Bösch, Kevin; Müller, Oliver (Hawaii International Conference on System Sciences)
Optimal decision making requires appropriate evaluation of advice. Recent literature reports that algorithm aversion reduces the effectiveness of predictive algorithms. However, it remains unclear how people recover from bad advice given by an otherwise good advisor. Previous work has focused on algorithm aversion at a single time point. We extend this work by examining successive decisions in a time series forecasting task using an online between-subjects experiment (N = 87). Our empirical results do not confirm algorithm aversion immediately after bad advice. The estimated effect suggests an increasing algorithm appreciation over time. Our work extends the current knowledge on algorithm aversion with insights into how weight on advice is adjusted over consecutive tasks. Since most forecasting tasks are not one-off decisions, this also has implications for practitioners.
Keywords: Algorithm aversion; Time series; Decision making; Advice taking; Forecasting

AI Washing: The Framing Effect of Labels on Algorithmic Advice Utilization - Leffrang, Dirk (International Conference on Information Systems)
Many researchers and practitioners see artificial intelligence as a game changer compared to classical statistical models. However, some software providers engage in “AI washing”, relabeling solutions that use simple statistical models as AI systems. By contrast, research on algorithm aversion unsystematically varied the labels for advisors and treated labels such as "artificial intelligence" and "statistical model" synonymously. This study investigates the effect of individual labels on users' actual advice utilization behavior. Through two incentivized online within-subjects experiments on regression tasks, we find that labeling human advisors with labels that suggest higher expertise leads to an increase in advice-taking, even though the content of the advice remains the same. In contrast, our results do not suggest such an expert effect for advice-taking from algorithms, despite differences in self-reported perception. These findings challenge the effectiveness of framing intelligent systems as AI-based systems and have important implications for both research and practice.
Keywords: Artificial Intelligence; Algorithm Appreciation; Framing; Advice-taking; Expertise

The Broken Leg of Algorithm Appreciation: An Experimental Study on the Effect of Unobserved Variables on Advice Utilization - Leffrang, Dirk (Wirtschaftsinformatik Conference)
Despite the widespread use of machine learning algorithms, their effectiveness is limited by a phenomenon known as algorithm aversion. Recent research concluded that unobserved variables can cause algorithm aversion. However, the impact of an unobserved variable on algorithm aversion remains unclear. Previous studies focused on situations where humans had more variables available than algorithms. We extend this research by conducting an online experiment with 94 participants, systematically varying the number of observable variables to the advisor and the advisor type. Surprisingly, our results did not confirm that an unobserved variable had a negative effect on advice-taking. Instead, we found a positive impact in an algorithm appreciation scenario. This study provides new insights into the paradoxical behavior in which people weigh advice more despite having fewer variables, as they correct for the advisor's errors. Practitioners should consider this behavior when designing algorithms and account for user correction behavior.
Keywords: Algorithm aversion; Data; Decision-making; Advice-taking; Human-Computer Interaction

Event Recommendations through the Lens of Vision and Language Foundation Models - Halimeh, Haya; Freese, Florian; Müller, Oliver (Workshop on Recommenders in Tourism, co-located with the 17th ACM Conference on Recommender Systems)
Recommender systems now span the entire customer journey. Amid the multitude of diversified experi- ences, immersing in cultural events has become a key aspect of tourism. Cultural events, however, suffer from fleeting lifecycles, evade exact replication, and invariably lie in the future. In addition, their low standardization makes harnessing historical data regarding event content or past patron evaluations intricate. The distinctive traits of events thereby compound the challenge of the cold-start dilemma in event recommenders. Content-based recommendations stand as a viable avenue to alleviate this issue, functioning even in scenarios where item-user information is scarce. Still, the effectiveness of content- based recommendations often hinges on the quality of the data representation they build upon. In this study, we explore an array of cutting-edge uni- and multimodal vision and language foundation models (VL-FMs) for this purpose. Next, we derive content-based recommendations through a straightforward clustering approach that groups akin events together, and evaluate the efficacy of the models through a series of online user experiments across three dimensions: similarity-based evaluation, comparison-based evaluation, and clustering assignment evaluation. Our experiments generated four major findings. First, we found that all VL-FMs consistently outperformed a naive baseline of recommending randomly drawn events. Second, unimodal text-based embeddings were surprisingly on par or in some cases even superior to multimodal embeddings. Third, multimodal embeddings yielded arguably more fine-grained and diverse clusters in comparison to their unimodal counterparts. Finally, we could confirm that cross event interest is indeed reliant on the perceived similarity of events, resonating with the notion of similarity in content-based recommendations. All in all, we believe that leveraging the potential of contemporary FMs for content-based event recommendations would help address the cold-start problem and propel this field of research forward in new and exciting ways.

Early Depression Detection with Transformer Models: Analyzing the Relationship between Linguistic and Psychology-Based Features - Halimeh, Haya; Caron, Matthew; Müller, Oliver (Hawaii International Conference on System Sciences)
Clinical depression is a serious mental disorder that poses challenges for both personal and public health. Millions of people struggle with depression each year, but for many, the disorder goes undiagnosed or untreated. Over the last decade, early depression detection on social media emerged as an interdisciplinary research field. However, there is still a gap in detecting hesitant, depression-susceptible individuals with minimal direct depressive signals at an early stage. We, therefore, take up this open point and leverage posts from Reddit to fill the addressed gap. Our results demonstrate the potential of contemporary Transformer architectures in yielding promising predictive capabilities for mental health research. Furthermore, we investigate the model’s interpretability using a surrogate and a topic modeling approach. Based on our findings, we consider this work as a further step towards developing a better understanding of mental eHealth and hope that our results can support the development of future technologies.
Keywords: Social Media and Healthcare Technology; early depression detection; liwc; mental health; transfer learning; transformer architectures

Analyzing the Needs of Ukrainian Refugees on Telegram in Real-Time: A Machine Learning Approach - Reimann, Raphael; Caron, Matthew (Wirtschaftsinformatik)
The humanitarian crisis resulting from the Russian invasion of Ukraine has led to millions of displaced individuals across Europe. Addressing the evolving needs of these refugees is crucial for hosting countries and humanitarian organizations. This study leverages social media analytics to supplement traditional surveys, providing real-time insights into refugee needs by analyzing over two million messages from Telegram, a vital platform for Ukrainian refugees in Germany. We employ Natural Language Processing techniques, including language identification, sentiment analysis, and topic modeling, to identify well-defined topic clusters such as housing, financial and legal assistance, language courses, job market access, and medical needs. Our findings also reveal changes in topic occurrence and nature over time. To support practitioners, we introduce an interactive web-based dashboard for continuous analysis of refugee needs.

Regenerative Energien für einen effizienten Betrieb von Presshärtelinien - Knorr, Lukas; Jungeilges, André; Pfeifer, Florian; Burmeister, Sascha Christian; Meschede, Henning

More Isn’t Always Better – Measuring Customers’ Preferences for Digital Process Transparency - Brennig, Katharina; Müller, Oliver (Hawaii International Conference on System Sciences)
Digital technologies have made the line of visibility more transparent, enabling customers to get deeper insights into an organization’s core operations than ever before. This creates new challenges for organizations trying to consistently deliver high-quality customer experiences. In this paper we conduct an empirical analysis of customers’ preferences and their willingness-to-pay for different degrees of process transparency, using the example of digitally-enabled business-to-customer delivery services. Applying conjoint analysis, we quantify customers’ preferences and willingness-to-pay for different service attributes and levels. Our contributions are two-fold: For research, we provide empirical measurements of customers’ preferences and their willingness-to-pay for process transparency, suggesting that more is not always better. Additionally, we provide a blueprint of how conjoint analysis can be applied to study design decisions regarding changing an organization’s digital line of visibility. For practice, our findings enable service managers to make decisions about process transparency and establishing different levels of service quality.
Keywords: Digital Services; Line of Visibility; Process Transparency; Customer Preferences; Conjoint Analysis

A Process Mining Maturity Model: Enabling Organizations to Assess and Improve their Process Mining Activities - Brock, Jonathan; Löhr, Bernd; Brennig, Katharina; Seger, Thilo; Bartelheimer, Christian; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (European Conference on Information Systems)
Organizations employ process mining to discover, check, or enhance process models based on data from information systems to improve business processes. Even though process mining is increasingly relevant in academia and organizations, achieving process mining excellence and generating business value through its application is elusive. Maturity models can help to manage interdisciplinary teams in their efforts to plan, implement, and manage process mining in organizations. However, while numerous maturity models on business process management (BPM) are available, recent calls for process mining maturity models indicate a gap in the current knowledge base. We systematically design and develop a comprehensive process mining maturity model that consists of five factors comprising 23 elements, which organizations need to develop to apply process mining sustainably and successfully. We contribute to the knowledge base by the exaptation of existing BPM maturity models, and validate our model through its application to a real-world scenario.

Text-Aware Predictive Process Monitoring of Knowledge-Intensive Processes: Does Control Flow Matter? - Brennig, Katharina; Benkert, Kay; Löhr, Bernd; Müller, Oliver (Business Process Management Workshops)

The Equivocal Image of Young Social Enterprises - How Self- vs. Other-Oriented Values Influence External Perceptions - Yahyaoui, Y.; Jakob, E.A.; Steinmetz, Holger; Wehner, M.C.; Isidor, R.; Kabst, Rüdiger (Nonprofit Management & Leadership)

Evaluation of product testing programs as an effective marketing tool - Negative and positive effects of rejections in product testing programs - Küpper, K.; Garnefeld, I.; Steinhoff, Lena

The Consumerization of Care: How Capitalism Is Co-Opting Solidarity - Alberternst, B.; Giesler, M.; Steinhoff, Lena

When Do Firms Highlight Their Effective Tax Rate? - Flagmeier, Vanessa; Müller, Jens; Sureth-Sloane, Caren (Accounting and Business Research)
This study examines GAAP effective tax rate (ETR) visibility as a distinct disclosure choice in firms’ financial statements. By applying a game-theory disclosure model for the voluntary disclosure strategies of firms, in a tax setting, we argue that firms face a trade-off in their ETR disclosure decisions. On the one hand, firms have an incentive to enhance their ETR disclosure when the ratio offers shareholders ‘favourable conditions’, for example, higher expected after-tax cash flows. On the other hand, the disclosure of a favourable low ETR could attract the attention of tax auditors and the public and ultimately result in disclosure costs. We empirically test disclosure behaviour by examining the relation between disclosure visibility and different ETR conditions that reflect different stakeholder-specific costs and benefits. While we find that unfavourable ETR conditions are not highlighted, we observe higher disclosure visibility for favourable ETRs (smooth, close to the industry average, and decreasing ETRs). Additional analyses reveal that this high visibility is characteristic of firm years with only moderately decreasing ETRs at usual ETR levels, while extreme ETRs are not highlighted. Interestingly and in contrast to our main results, a subsample of family firms does not seem to highlight favourable ETRs.

Losses Never Sleep – The Effect of Tax Loss Offset on Stock Market Returns during Economic Crises - Koch, Reinald; Holtmann, Svea; Giese, Henning (Journal of Business Economics)

The Tax Complexity Index – A Survey-Based Country Measure of Tax Code and Framework Complexity - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren (European Accounting Review)

Customer Misbehavior in the Peer-to-Peer Sharing Economy: The Mixed Role of Face-to-Face Interactions - Ozuna, Edna; Steinhoff, Lena

Face-to-Face Interactions in Peer-to-Peer Sharing Economy Services: An Effective Barrier to Customer Misbehavior? - Ozuna, Edna; Steinhoff, Lena

Umfrage: Tax Compliance und Verrechnungspreise - Greil, Stefan; Kaluza-Thiesen, Eleonore; Schulz, Kim Alina; Sureth-Sloane, Caren

GBP-Monitor Q3/2023: Das Wachstumschancengesetz – ein Investitionsimpuls? - Maiterth, Ralf; Sureth-Sloane, Caren; Dyck, Daniel; Heinemann-Heile, Vanessa (Schmalenbach IMPULSE)

Umfrage: Bewertung Investitionsfördernder Maßnahmen durch Unternehmen aus Handel, Dienstleistung und Industrie - Heinemann-Heile, Vanessa; Maiterth, Ralf; Sureth-Sloane, Caren

Umfrage: Beurteilung Investitionsfördernder Maßnahmen durch Unternehmen im Handwerk - Heinemann-Heile, Vanessa; Maiterth, Ralf; Sureth-Sloane, Caren

Open Educational Resources zur Förderung nachhaltiger Bildung und Forschung. In: Jahrestagung 2023 der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaften - Schneider, Jennifer Nicole

SAFE -Streaming approaches for Europe - Enhancing the digital competences by streaming approaches for schools to tackle the challenges of COVID-19. The Teacher-Training-Platform on the SAFE Project Website - Schneider, Jennifer Nicole

SAFE -Streaming approaches for Europe - Enhancing the digital competences by streaming approaches for schools to tackle the challenges of COVID-19. Administrative and financial information - Schneider, Jennifer Nicole

Green-4-Future – Project Insights to its best! In: Training and Cooperation Activity (TCA) “Green Erasmus: pathways to sustainable projects and institutions” - Schneider, Jennifer Nicole

Green-4-Future. Learning/Teaching/Training Activity –Transnational Training Event LTTA1. Business CANVAS Model – in Green Entrepreneurships - Schneider, Jennifer Nicole

Game Studies – Role Play in Therapy and Education. Pen and Paper Congress.Vortrag: Potenziale von Open Educational Resources bei Pen& Paper Rollenspielen in der Bildungspraxis nutzen! – Warum und wie soll das gehen?! - Schneider, Jennifer Nicole

Green-4-Future. Learning/Teaching/Training Activity –Transnational Training Event LTTA2. Creative Thinking – in Green Entrepreneurships - Schneider, Jennifer Nicole

STEMinAction- Final Project Meeting – Unlocking Long-Term Sustainability: Harnessing Open Educational Resources (OER) Beyond Project Lifetimes - Schneider, Jennifer Nicole

Green-4-Future. Learning/Teaching/Training Activity –Transnational Training Event LTTA1. Use, sharing and creating Open Educational Resources – Why is it so important? - Schneider, Jennifer Nicole

SAFE -Streaming approaches for Europe - Enhancing the digital competences by streaming approaches for schools to tackle the challenges of COVID-19. The SAFE Learning Videos - Schneider, Jennifer Nicole

Gestaltung von Open Educational Resources zur Förderung von Nachhaltigkeit in Bildung und Wirtschaft - Schneider, Jennifer Nicole (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Green-4-Future. Learning/Teaching/Training Activity –Transnational Training Event LTTA1. Creative Thinking – in Green Entrepreneurships - Schneider, Jennifer Nicole

SAFE -Streaming approaches for Europe - Enhancing the digital competences by streaming approaches for schools to tackle the challenges of COVID-19 - Schneider, Jennifer Nicole

Der Wirtschaft auch in der Krise das Atmen erlauben, Pandemie und Ökonomie – Interview mit Steuerexpertin Caren Sureth-Sloane - Unterstell, Rembert (forschung - Das Magazin der Deutschen Forschungsgemeinschaft)

Workarounds as generative mechanisms for bottom‐up process innovation—Insights from a multiple case study - Bartelheimer, Christian; Wolf, Verena; Beverungen, Daniel (Information Systems Journal)
Abstract Workarounds are goal‐driven deviations from the standard operating procedures performed to overcome obstacles constraining day‐to‐day work. Despite starting as temporary fixes, they can become established across an organisation and trigger the innovation of processes and IT artefacts that can resolve misfits permanently. Although prior research has elicited antecedents and types of workarounds, it is not known how workarounds diffuse in an organisation and, thereby, innovating co‐workers' activities, IT artefacts, and organisational structures. The results of our multiple two‐year case study provide unique empirical insights into the diffusion of workarounds and how they can act as generative mechanisms for bottom‐up process innovation.
Keywords: Computer Networks and Communications; Information Systems; Software

“Sorry, Too Much Information”. Designing Online Review Systems that Support Information Search and Processing - Seutter, Janina; Kutzner, K.; Stadtländer, M.; Kundisch, Dennis; Knackstedt, R. (Electronic Markets)

Verdrängen Smart-Product-Service-Systeme die Interaktion in Online-Communities? – Empirische Evidenz aus einer Rezept-Community - Seutter, Janina; Müller, Michelle; Kundisch, Dennis (Wirtschaftsinformatik & Management)

Comparing Humans and Algorithms in Feature Ranking: A Case-Study in the Medical Domain - Hanselle, Jonas; Kornowicz, Jaroslaw; Heid, Stefan; Thommes, Kirsten; Hüllermeier, Eyke (Lernen, Wissen, Daten, Analysen (LWDA) Conference Proceedings)
The selection of useful, informative, and meaningful features is a key prerequisite for the successful application of machine learning in practice, especially in knowledge-intense domains like decision support. Here, the task of feature selection, or ranking features by importance, can, in principle, be solved automatically in a data-driven way but also supported by expert knowledge. Besides, one may of course, conceive a combined approach, in which a learning algorithm closely interacts with a human expert. In any case, finding an optimal approach requires a basic understanding of human capabilities in judging the importance of features compared to those of a learning algorithm. Hereto, we conducted a case study in the medical domain, comparing feature rankings based on human judgment to rankings automatically derived from data. The quality of a ranking is determined by the performance of a decision list processing features in the order specified by the ranking, more specifically by so-called probabilistic scoring systems.

The use of IT and OER to support remote sustainable work in Europeans Green Economy - Beutner, Marc; Schneider, Jennifer Nicole (International Conference on Industry Sciences and Computer Science Innovation)

Open Educational Resources in der beruflichen Bildungslandschaft - Schneider, Jennifer Nicole

Der Wirtschaft auch in der Krise das Atmen erlauben, Pandemie und Ökonomie – Interview mit Steuerexpertin Caren Sureth-Sloane - Unterstell, Rembert

Allowing the Economy to Breathe Even During the Crisis – Interview with Tax Expert Caren Sureth-Sloane - Unterstell, Rembert

TPACK, DPACK, XY-Pack? Eine kritische Auseinandersetzung mit der Modellierung digitaler Inhaltskompetenzen für die berufliche Bildung - Sänger, Niklas; Jenert, Tobias (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Das TPACK-Modell wird häufig zur Konzeptualisierung digitaler Kompetenzen in der Lehrer:innenbildung herangezogen. Es stellt die Bezüge des Lehrer:innenwissens zwischen den Dimensionen des inhaltlichen, pädagogischen und technologischen Wissens her. Wir analysieren in diesem Beitrag die Passung von TPACK zur Modellierung digitaler Kompetenzen für den Kontext der beruflichen Bildung, insb. mit Blick auf die Inhaltsdimension. Wir argumentieren, dass TPACK und solche Modelle, die sich daran anlehnen, den doppelten inhaltlichen Gegenstandsbezug der beruflichen Bildung nicht hinreichend abbilden. Darauf aufbauend diskutieren wir mögliche Weiterentwicklungen des Modells für die berufliche Bildung sowie dessen Bedeutung für die berufliche Lehrer:innenbildung.

Evidenzbasierte Hochschuldidaktik - Scharlau, Ingrid; Jenert, Tobias (Hochschuldidaktik als Wissenschaft: Disziplinäre, interdisziplinäre und transdisziplinäre Perspektiven)

TPACK, DPACK, XY-PACK? Eine kritische Auseinandersetzung mit der Modellierung digitaler Inhaltskompetenzen für die berufliche Bildung - Sänger, Niklas

Der Einsatz von didaktischen Fallstudien zur Erkundung digital transformierter Arbeits- und Geschäftsprozesse im Studienfach Wirtschaftswissenschaft für das Lehramt an Berufskollegs - Sänger, Niklas

Didaktische Fallstudien zur exemplarischen Erkundung der digitalen Transformation der Arbeits- und Geschäftsprozesse im Studienfach Wirtschaftswissenschaft für das Lehramt an Berufskollegs - Sänger, Niklas

Technological Pedagogical Content Framework for the Vocational Teacher Education in Germany - Sänger, Niklas

Vorstellung eines Trainings zur Förderung des selbstregulierten unternehmerischen Lernens in der Entrepreneurship-Education. - Büker, Ronja; Jenert, Tobias; Fahrbach, Manuel (Jahrestagung der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft)

TPACK, DPACK, XY-PACK? Eine kritische Auseinandersetzung mit der Modellierung digitaler Inhaltskompetenzen für die berufliche Bildung - Sänger, Niklas; Jenert, Tobias; Kremer, H.-Hugo (Jahrestagung der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft)